2015
DOI: 10.1007/s00424-014-1675-z
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study

Abstract: It has long been held that electrical excitation spreads from cell-to-cell in the heart via low resistance gap junctions (GJ). However, it has also been proposed that myocytes could interact by non-GJ-mediated “ephaptic” mechanisms, facilitating propagation of action potentials in tandem with direct GJ-mediated coupling. We sought evidence that such mechanisms contribute to cardiac conduction. Using super-resolution microscopy, we demonstrate that Nav1.5 is localized within 200 nm of the GJ plaque (a region te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
260
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(291 citation statements)
references
References 45 publications
30
260
0
1
Order By: Relevance
“…In particular a population of Nav1.5 is located at the periphery of gap junctions in a so-called perinexus region that has been proposed to be involved in ephaptic conduction. 102 It might be possible that constitutive deletion of SAP97 led to compensatory modifications in the expression and/or organization of one more partner proteins that contributed to maintain Na V 1.5 expression.…”
Section: Potassium Channel Macromolecular Complexes and Associatedmentioning
confidence: 99%
“…In particular a population of Nav1.5 is located at the periphery of gap junctions in a so-called perinexus region that has been proposed to be involved in ephaptic conduction. 102 It might be possible that constitutive deletion of SAP97 led to compensatory modifications in the expression and/or organization of one more partner proteins that contributed to maintain Na V 1.5 expression.…”
Section: Potassium Channel Macromolecular Complexes and Associatedmentioning
confidence: 99%
“…Experiments using genetically engineered ventricular and atrial mouse myocytes suggest that about 50% of Na v 1.5 channels are located in the intercalated disc, [66][67][68][69][70] whereby a fraction of these channels resides in close vicinity of gap junction plaques, the so-called perinexus. Early work by N. Sperelakis and more recent computer simulations [71][72][73][74][75] suggested that these channels may contribute the cell-to-cell transfer of cardiac impulses in presence of limited or in absence of cell-to-cell coupling by gap junctions. 76 Currently, experiments carried out at the cellular level are needed to provide an answer to this interesting hypothesis.…”
Section: Limitations Of Experimental Models and Perspectivementioning
confidence: 99%
“…Однако позднее была показана колокализация Na v 1.5 с щелевыми контактами во вставочных дисках [22]. В действи-тельности макромолекуляный комплекс коннексо-на находится в тесном взаимодействии с натрие-выми каналами и десмосомами [23][24][25][26][27][28][29]. Морфоло-гические исследования подтверждают идею о том, что компоненты макромолекулярного комплекса коннексонов взаимодействуют между собой, а у пациентов с синдромом Бругада отмечается умень-шение количества щелевых контактов и увеличе-ние количества фиброзных структур с отложением коллагена в выходящем тракте правого желудочка [30,31].…”
Section: том 4 №4 / 2017unclassified